Decentralizing university admission: Evidence from a natural experiment - Julia Horstschräer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Applying a differences-in-differences strategy, I study the decentralization of university admission as a natural experiment. Is the centralized or decentralized procedure better suited to match prospective students to universities? The analysis uses administrative data on all students within Germany and complements the prominent theoretical literature on college admission. The results show that the matching efficiency increased in course of the decentralization. This increase is mainly driven by enabling law schools to abolish admission restrictions. The matching quality is not significantly affected by the decentralization process but suggests that abolishing admission restrictions could be associated with increasing drop-out rates.
urn:nbn:de:bsz:180-madoc-326704
Keywords: I21; I23; C21; 330; higher education; college admission problem; university admission; Hochschule; Studienfach; Angebot; Zentrale Organisation; Dezentrale Organisation; Studierende; Nachfrage; Matching; Deutschland